DUALarm: An open-source and 3D-printable device for upper limb neurorehabilitation. (January 2018) - Dinon, Tito; Caimmi, Marco; Chiavenna, Andrea; Malosio, Matteo; Prini, Alessio; Scano, Alessandro; Molinari Tosatti, Lorenzo; Currò, Cristian; Lenzi, Bruno; Megale, Valentino
Positively advocating that low-cost additive 3D-printing technologies and open-source licensed software/hardware platforms represent an optimal solution to realize low-cost equipment, a mechanical and 3D-printable device for bilateral upper-limb rehabilitation is presented. The design and manufacturing process of this wheel-geared mechanism, enabling in-phase and anti-phase movements, will be openly provided online with the aim of making a set of customizable devices for neurorehabilitation exploitable all over the world even by people/countries with limited economical and technological resources. In order to characterize the interaction with the device, preliminary trials with EMG and kinematics recordings were performed on healthy subjects.